Relationship between fine aggregate size and the air void system of six mortars: I. Air void content and diameter distribution. (August 2022) - Lyu, Kai; Garboczi, E.J.; Gao, Yufeng; Miao, Changwen; Liu, Xiaoyan
Abstract: Precisely determining the characteristics of the air void system in cement-based materials is important in material design and freeze-thaw durability evaluation. X-ray computed tomography (XCT) has been used to characterize air void systems, since it is able to measure the 3D spatial arrangement of the voids. Though the factors influencing air void formation and arrangement have been well-studied, the role of fine aggregate size and gradation has mainly been ignored. In this paper, six mortars were prepared with varying sand size distributions and their air void system quantitatively characterized via XCT. The role of sand size distribution and blended proportions were combined via calculation of the fine aggregate specific surface area ( SSA ). A linear relationship between SSA and global air void volume fraction was observed, with increasing air void volume fraction as SSA increased (and sand size decreased). The 2D circle diameter distribution was derived from 2D analysis of each XCT slice and the 3D sphere diameter distribution was derived from 3D analysis of the stacked 3D XCT microstructure. The distributions for 2D and 3D were calculated from each other using stereological methods and compared with the original experimental results. All three methods used were in reasonable agreement. The air void size distributions obtained via high resolution (small voxel size, small scan volume) and low resolution (large voxel size, large scan volume) XCT scans compared favorably in a compatible air void size range, which illustrates how the problems of differing XCT resolutions can be resolved.